Strategic Alliances and Firm Innovation in Global Markets in Turkey - Tekin, Hasan (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to investigate the strategic alliances and firm innovation in global markets in Turkey. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Strategic alliances significantly enhance firm innovation in global markets, particularly in Turkey. These partnerships enable firms to access resources and knowledge, driving innovation through joint R&D and technological advancements. In Turkey, alliances with multinational corporations and global partners accelerate technology adoption and best practices, boosting local firms' innovation capabilities and expanding market reach. Despite challenges like cultural differences and regulatory issues, effective alliance management can greatly benefit firms by improving competitiveness and innovation outcomes globally. Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV) theory, transaction cost economics (TCE) theory & social network theory may be used to anchor future studies on strategic alliances and firm innovation in global markets in Turkey. Enhance organizational capabilities in alliance management through training programs and knowledge-sharing platforms that emphasize best practices in partner selection, negotiation, and collaborative innovation. Develop supportive regulatory frameworks that encourage cross-border alliances and facilitate intellectual property protection, thereby reducing legal uncertainties and enhancing trust among international partners.